Implementasi Penarapan Business Model Canvas (BMC) pada perusahaan Properti di Tangerang Selatan: Pengabdian - Jonathan; Haris Hartadi; M. Rachman Mulyandi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service was conducted to conduct a Business Model Canvas (BMC) design study for a partner project, namely residential property development in the Pamulang area, South Tangerang. The study focused on the integration of economic, social and environmental values. The methods used include descriptive case study techniques, interviews, and document analysis. The results of this study indicate that the partner's BMC can align profitability with sustainability through strategically located eco-friendly housing, clear customer segments, integrated distribution channels, and the establishment of key partnerships. The primary revenue streams come from sales and rentals, with the overall cost structure focused on construction and operational expenses. The designed BMC is expected to serve as a strategic guide capable of enhancing the profitability of the partner's projects while contributing to environmental.